Performance Comparison of HFC and FTTH Using Optisystem Software - Dwi Permana Putra; Marsul Siregar; Lanny Pandjaitan; Karel O Bachri; Catherine O Sereati (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2025)
This research present the Analysis of the application of Optisystem software technology for FTTH and HFC shows that both have the capability for the WDM systems, to support a maximum transmission distance of 20 kilometers and can serve up to 32 subscribers. Key factors such as signal strength, Q factor, and bit error rate (BER) were observed and analyzed discreetly. It was found that FTTH has an average Q factor of 13.49 and HFC has an average Q factor of 7.475. The difference is about 44.59%, which indicates that FTTH has an advantage in terms of signal quality. However, based on the simulation results as well as the field measurements, Since the BER value does not exceed the maximum limit of 10-9 and the Q-factor value exceeds the minimum limit of 6, it can be stated that both technologies are reliable for efficient and high-quality communication services.